Alleviation of thalamic pain by cilostazol administration: a case report. Issue 2 (10th January 2018) - Haruta‐Tsukamoto, Ayaka; Funahashi, Hideki; Miyahara, Yu; Matsuo, Tomoko; Nishimori, Toshikazu; Ishida, Yasushi
Key Clinical Message: Thalamic pain is severe and treatment‐resistant; however, there are few available options for improving thalamic pain. This study demonstrated that thalamic pain was alleviated by administration of cilostazol, suggesting that cilostazol may be a candidate for treating thalamic pain. Abstract : Thalamic pain is severe and treatment‐resistant; however, there are few available options for improving thalamic pain. This study demonstrated that thalamic pain was alleviated by administration of cilostazol, suggesting that cilostazol may be a candidate for treating thalamic pain.